2013
DOI: 10.1002/oby.20441
|View full text |Cite
|
Sign up to set email alerts
|

Surgical control of obesity and diabetes: The role of intestinal vs. gastric mechanisms in the regulation of body weight and glucose homeostasis

Abstract: Objective: To elucidate the specific role of gastric vs. intestinal manipulations in the regulation of body weight and glucose homeostasis. Design and Methods: The effects of intestinal bypass alone (duodenal-jejunal bypass -DJB) and gastric resection alone (SG) in Zucker Diabetic Fatty (ZDF) rats were compared. Additional animals underwent a combination procedure (SG þ DJB). Outcome measures included changes in weight, food intake (FI), oral glucose tolerance (GT) and gut hormones. Results: DJB did not substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 44 publications
4
23
0
1
Order By: Relevance
“…The GIP response to the oral glucose load was similarly unaffected by these procedures, suggesting that, at least in these animals, the effect of these operations is not mediated by changes in these incretins. These results are consistent with those of at least two recent studies (10,38) showing that GLP-1 levels are not dramatically elevated shortly after DJB. This is in contrast with the evidence that RYGB and sleeve gastrectomy result in rapid and large elevations of GLP-1 in response to oral glucose or mixed-meal tests both in humans and rodents.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The GIP response to the oral glucose load was similarly unaffected by these procedures, suggesting that, at least in these animals, the effect of these operations is not mediated by changes in these incretins. These results are consistent with those of at least two recent studies (10,38) showing that GLP-1 levels are not dramatically elevated shortly after DJB. This is in contrast with the evidence that RYGB and sleeve gastrectomy result in rapid and large elevations of GLP-1 in response to oral glucose or mixed-meal tests both in humans and rodents.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy might be due to the fact that RYGB and sleeve gastrectomy, unlike DJB, involve significant manipulations of gastric anatomy. In fact, a recent study (38) suggests that changes in GLP-1 response to nutrient stimuli may result from alterations of gastric physiology rather than from intestinal rerouting as previously believed.…”
Section: Discussionmentioning
confidence: 92%
“…In the study by Hu et al 11 , DJB was also unable to reduce the body weight of animals previously fed with a highcalorie diet and a standard diet for 12 weeks after surgery. According to Patel et al 21 , rats submitted to DJB showed no changes in the concentration of fasting ghrelin, a hormone involved in regulating food intake. Thus, it is suggested that animals did not lose weight after DJB because this surgical procedure does not provoke a change in food intake.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Also, recent studies using mice models of functional GLP-1 deficiency, GLP-1 receptor knockout mice (20), and inhibition of GLP-1 receptor by exendin(9-39) in humans (21) call into question the role of GLP-1, suggesting that the mechanisms of action of RYGB are more complex. RYGB excludes the duodenum and jejunum from the transit of nutrients, which seems to have specific antidiabetes effects (22,23). Given the close anatomic relationship between the duodenum and the pancreas, one cannot exclude that changes in regional/paracrine neuroendocrine mechanisms could also influence b-cell function and growth.…”
mentioning
confidence: 99%
“…RYGB excludes the duodenum and jejunum from the transit of nutrients, which seems to have specific antidiabetes effects (22,23). Given the close anatomic relationship between the duodenum and the pancreas, one cannot exclude that changes in regional/paracrine neuroendocrine mechanisms could also influence b-cell function and growth.…”
mentioning
confidence: 99%